Sorgo em dietas para juvenis de Rhamdia quelen suplementadas com fitase - Rodrigues, Mariana Lins (2017)
The present study aimed to evaluate the productive performance of silver catfish juveniles fed with diets containing different sorghum inclusion levels as a substitute of maize, and supplemented or not with the phytase enzyme. The diets were composed of maize, maize/sorghum and sorghum, supplemented or not with phytase enzyme (1500 UFA/kg-1). Apparent feed conversion and specific growth rate were better for supplemented diets (P<0.05). The larger protein efficiency rate was obtained for maize diet supplemented (P<0.05). The viscerosomal fat index was lower when maize/sorghum diet was used (P<0.05), whereas the hepatosomatic index was smaller for maize and maize/sorghum diets, regardless of supplementation (P <0.05). The plasmatic biochemical components presented variation (P <0.05), but they remained within the limits of the species. The histomorphometric variables presented variations for sorghum and sorghum/maize diets, supplemented or not (P<0.05). The chemical composition of the carcass presented variations related to ethereal extract and mineral matter deposition for supplemented diets (P<0.05). In bone mineralization there was a variation of Ca (P<0.05) when maize and sorghum were used in the same proportion. Therefore, sorghum may be a viable alternative to maize substitution, and phytase supplementation improves the productive performance of fish.